Two Distinct Genotypes of KPC-2-Producing Klebsiella pneumoniae Isolates from South Korea - Jee Hong Kim; Yun Young Cho; Ji Young Choi; Yu Mi Wi; Kwan Soo Ko (Antibiotics, 2021)
In this study, we investigated the characteristics of KPC-2-producing Klebsiella pneumoniae (KP-Kp) isolates from a hospital in South Korea. Among the 37 KP-Kp isolates, two main clones were identified—ST11 and ST307. ST11 isolates showed higher minimum inhibitory concentrations for carbapenems than ST307 isolates. All ST307 isolates were resistant to gentamicin and trimethoprim–sulfamethoxazole, but ST11 isolates were not. However, most tigecycline-resistant or colistin-resistant isolates belonged to ST11. The two KP-Kp clones showed different combinations of wzi and K serotypes. Plasmids from ST11 KP-Kp isolates exhibited diverse incompatibility types. Serum resistance and macrophage infection assays indicated that ST11 may be more virulent than ST307. The changes in the main clones of KP-Kp isolates over time as well as the different characteristics of these clones, including virulence, suggest the need for their continuous monitoring.